Preclinical safety and effectiveness studies of ultrasonic propulsion of kidney stones - Harper, Jonathan D. (Urology, 2014)
OBJECTIVE: To provide an update on a research device to ultrasonically reposition kidney stones transcutaneously. This paper reports preclinical safety and effectiveness studies, survival data, modifications of the system, and testing in a stone-forming porcine model. These data formed the basis for regulatory approval to test the device in humans. MATERIALS AND METHODS: The ultrasound burst was shortened to 50ms from previous investigations with 1s bursts. Focused ultrasound was used to expel 2–5mm calcium oxalate monohydrate stones placed ureteroscopically in five pigs. Additionally, de novo stones were imaged and repositioned in a stone-forming porcine model. Acute safety studies were performed targeting two kidneys (6 sites) and three pancreases (8 sites). Survival studies followed 10 animals for one week after simulated treatment. Serum and urine analyses were performed and tissues were evaluated histologically. RESULTS: All ureteroscopically-implanted stones (6/6) were repositioned out of the kidney in 14 ± 8 minutes with 13 ± 6 bursts. On average, three bursts moved a stone more than 4mm and collectively accounted for the majority of relocation. Stones (3mm) were detected and repositioned in the 200-kg stone-forming model. No injury was detected in the acute or survival studies. CONCLUSIONS: Ultrasonic propulsion is safe and effective in the porcine model. Stones were expelled from the kidney. De novo stones formed in a large porcine model were repositioned. No adverse effects were identified with the acute studies directly targeting kidney or pancreatic tissue or during the survival studies indicating no evidence of delayed tissue injury.